NEUROPSYCHOLINGUISTICS OF CHILDREN WITH AUTISM SPECTRUM DISORDER (ASD): UNDERSTANDING COMMUNICATION IN DAILY LIFE AND TREATMENT MEDIA - Sinaga, Septian Immanuel; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2025)
Autism spectrum disorder (ASD) is a type of developmental disorder that is influenced by biological factors and affects children's social interactions and communication skills. For children with ASD, communication challenges are often one of the main aspects faced. Therefore, communication skills are considered an important indicator in assessing their developmental progress. The purpose of this study was to understand how children with autism spectrum disorder communicate in their daily lives and to find out how treatment media can be used to help them. The method used is a literature review that analyzes various journals, articles, and books from Google Scholar, Academia.edu, and ResearchGet. Research has found that the impact of autism on communication skills is often significant, making it difficult for individuals to form meaningful interactions and relationships with others. Treatment media can be done by using speech therapy, occupational therapy, and using visual media to help children with autism communicate well in their daily lives.